2012
DOI: 10.1159/000345492
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Drusen and Geographic Atrophy Area Size after Cataract Surgery Using the MD3RI Tool for Computer-Aided Contour Drawing

Abstract: Background/Aims: To monitor possible changes in the cumulated drusen or geographic atrophy area size (CDGAS) of nonexudative age-related macular degeneration (AMD) in patients before and after cataract surgery, using a new tool for computer-aided image quantification. Methods: Randomized, prospective, clinical trial. 54 patients with cataract and nonexudative AMD were randomly assigned into an early surgery group (ES = 28) and a control group (CO = 26) with a 6-month delay of surgery. CDGAS was determined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 72 publications
(56 reference statements)
0
30
0
1
Order By: Relevance
“…Of 788 unique records newly identified, we excluded 787 records by screening the titles and abstracts and included one study report (Brunner 2013). This study report included the results from the ongoing study previously identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 788 unique records newly identified, we excluded 787 records by screening the titles and abstracts and included one study report (Brunner 2013). This study report included the results from the ongoing study previously identified.…”
Section: Resultsmentioning
confidence: 99%
“…The two trials (114 eyes of 114 participants) included in this review enrolled participants with cataract and AMD; however, Brunner 2013 included only participants with non-exudative AMD, and Lamoureux 2007 included only participants with Age-Related Eye Disease Study (AREDS) category 3 AMD in the study eye. In both trials, participants were randomized to immediate cataract surgery (within two weeks of enrollment) (n = 57) or delayed cataract surgery (six months after enrollment) (n = 57).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, news tools as the MD3RI software (a computer-aided image quantification) do not found changes in Cumulated Drusen or Geographic Atrophy area Size (CDGAS) after 12 months of cataract surgery [33]. Conversely, Pipis et al, utilize modern software integrated to optical coherence tomography (advanced software of RPE) and suggest that blue light-filtering intraocular lenses have a significant photoprotective effect on the progression of geographic atrophy after cataract surgery [34].…”
Section: Geographic Amdmentioning
confidence: 99%
“…As 61 imagens da retina centradas na zona macular utilizadas neste estudo foram obtidas a partir do trabalho efetuado por Simmon Brunner "ECAM -Monitoring Drusen and Geographic Atrophy after Cataract Surgery Study" (Brunner et al, 2013). Todas as imagens foram captadas no Departmento de Oftalmologia do Rudolfstiftung Hospital, Vienna, Austria usando um retinógrafo de 40º (Canon CR2-45NM, Veatch Ophthalmic Instruments) e digitalizadas com uma resolução de 1639x1116 pixéis.…”
Section: Imagens Utilizadasunclassified